Understanding Digital Literacy Training Success: An Exploration Across Canada - Detlor, Brian; Julien, Heidi (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2020)
This paper reports progress of a SSHRC-funded research investigation that studies the factors affecting the success of digital literacy skills training offered by community-led organizations, such as public libraries, across Canada. The goal of the study is to identify best practices. The study also seeks to contribute to the theoretical understanding of digital literacy instruction led by community organizations. This paper reports preliminary results of the analysis of interviews with administrators and instructors from organizations in Canada which offer such training, as well as from interviews and surveys collected from people who took part in these organizations’ training activities. Cet article fait état de l'avancement d'une recherche financée par le CRSH qui étudie les facteurs influant sur le succès de la formation en littératie numérique offerte par des organismes communautaires, comme les bibliothèques publiques, partout au Canada. Le but de l'étude est d'identifier les meilleures pratiques. L'étude cherche également à contribuer à la compréhension théorique de l'enseignement de la littératie numérique menée par des organisations communautaires. Cet article présente les résultats préliminaires de l’analyse des entrevues avec des administrateurs et des formateurs d’organismes au Canada qui offrent une telle formation, ainsi que des entrevues et des sondages recueillis auprès de personnes ayant participé aux activités de formation de ces organismes.